Hubungan Kemampuan Sintaksis dengan Kemampuan Literasi Awal pada Anak Kelas 2 SD Negeri 1 Pilang Randublatung Blora - Aziza, Yamania Urfi; Sutanto, Alfiani Vivi (Jurnal Terapi Wicara dan Bahasa, 2024)
Background: Literacy is a very important issue in the era of Industrial Revolution 4.0. PISA (Program for International Student Assessment) states that Indonesia is ranked 64 out of 65 countries in terms of literacy in children. To develop literacy skills from an early age, children must be encouraged to engage in lifelong learning (UNESCO, 2017). In literacy there are aspects of language that influence reading, namely syntax. This syntactic ability has an important role in early child development, This is needed so that children can compose sentences in a good and correct structure. Objectives: This Research to determine the correlation between syntactic skills and early literacy skills in grade 2 children at SD Negeri 1 Pilang, Randublatung, Blora. Methods: The type of research used in this study is quantitative with Cross sectional research design. The population of this study was grade 2 students at SD Negeri 1 Pilang, Randublatung, Blora. The study sample was 54 grade 2 children. Data analysis using Kendall Tau Test. Results: The results of the analysis showed that there was a relationship between syntactic skills and early literacy skills in grade 2 children at SD Negeri 1 Pilang, Randublatung, Blora (p value of 0.000). Conclusion: There is a relationship between syntactic skills and early literacy skills in grade 2 children at SD Negeri 1 Pilang, Randublatung, Blora. Keywords : Syntax, Early Literacy, SchoolAge Children